Correlating Carbon Dioxide Capture and Chemical Changes in Pyrolyzed Polyethylenimine-C60 - Enrico Andreoli (Energy & Fuels, 2015)
Nitrogen functionalities play a crucial role in determining the sorption capacity and selectivity of organic-based CO2 solid sorbents. Two main types of solid sorbents are (1) amine-rich compounds used for their distinctive reactivity of amino groups with CO2, and (2) N-doped carbons where CO2-philic nitrogens impart chemoselectivity to otherwise pure carbon physisorbents. It is of interest to correlate the CO2 sorption performance of these materials to the chemical changes involved in going from amine-rich polymers to N-doped carbons. To this end, we pyrolyzed amine-rich polyethylenimine-C60 (PEI-C60) to N-doped carbons and focused our investigation on how chemical changes and CO2 capture correlate. In particular, we found that upon thermal treatment in inert atmosphere, PEI-C60 undergoes an inversion in CO2 sorption behavior. PEI-C60, which better absorbs CO2 at high temperature (0.13 g/g at 90 °C), is converted into pyrolyzed materials with improved CO2 capture performance at low temperature (0.12 g/g at 25 °C). X-ray photoelectron spectroscopy (XPS), Fourier transfer infrared (FTIR), and Raman characterizations reveal a progressive conversion of PEI-C60 to disordered graphitic carbon including pyrrolic and pyridinic aromatic nitrogens, where the transition from one material to the other goes through a drastic drop of CO2 capture performance due to the breakdown of the carbon backbone of PEI.